2020
DOI: 10.14233/ajchem.2021.22928
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid, Phytochemical Compositions and Antioxidant Activity of Inky Cap Mushroom (Coprinus radiata)

Abstract: Evaluation of the amino acid composition, phytochemical properties and antioxidant activity of Coprinus radiata mushrooms was conducted. Free amino acid composition of fresh mushrooms was analyzed by LC-MS/MS. The phytochemical properties analysis included total phenolic compound content and total flavonoid content of these mushrooms. Furthermore, antioxidant activity assays were performed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP). Based on the results shown that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The methanolic, ethanolic, and aqueous extracts of P. ostreatus and P. florida possess alkaloids, tannins, and saponins [ 85 ]. The highest TPC concentration was observed in the methanolic extract in both P. ostreatus and P. florida compared to the other solvents, and the concentration was comparable [ 86 ]. On the other hand, steroids are exclusively identified in P. ostreatus within all extracts [ 85 ].…”
Section: Phytochemical Investigationsmentioning
confidence: 99%
See 3 more Smart Citations
“…The methanolic, ethanolic, and aqueous extracts of P. ostreatus and P. florida possess alkaloids, tannins, and saponins [ 85 ]. The highest TPC concentration was observed in the methanolic extract in both P. ostreatus and P. florida compared to the other solvents, and the concentration was comparable [ 86 ]. On the other hand, steroids are exclusively identified in P. ostreatus within all extracts [ 85 ].…”
Section: Phytochemical Investigationsmentioning
confidence: 99%
“…In a comparison of two extraction methods, ethanol and aqueous extraction, the total phenolic content (TPC) of the inky cap mushroom ( C . radiata ) was analyzed [ 86 ]. The results indicated that the ethanol extract had a higher TPC than the aqueous extract [ 86 ].…”
Section: Phytochemical Investigationsmentioning
confidence: 99%
See 2 more Smart Citations